1999
DOI: 10.1097/00000374-199902000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naltrexone on Alcohol Self-Administration in Heavy Drinkers

Abstract: The mechanisms underlying the suppressant effects of naltrexone (NTX) on ad libitum alcohol drinking in a bar/restaurant setting were investigated in heavy beer drinkers. Fifty-one male and female heavy drinkers (mean age = 22) received 50 mg of NTX or placebo (PBO), p.o., on two separate occasions in a randomized, double-blind crossover protocol. After 7 days of taking medication, subjects were provided with the opportunity to consume beer ad libitum during two, 90-min test sessions that were held 1 to 2 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 0 publications
4
42
1
1
Order By: Relevance
“…In that study, NTX treatment was discontinued in 15.0% of patients because of adverse events, most frequently nausea. However, studies of former opioid addicts (Crowley et al 1985), normal control subjects (Swift et al 1994, Mendelson et al 1979, and heavy drinkers (Davidson et al 1999) have shown the drug to produce substantial rates of both neuropsychiatric and gastrointestinal adverse effects. Overall, it seems that, irrespective of diagnosis, there are substantial numbers of individuals who experience dysphoria, nausea, and other poorly tolerated adverse effects of opioid blockade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, NTX treatment was discontinued in 15.0% of patients because of adverse events, most frequently nausea. However, studies of former opioid addicts (Crowley et al 1985), normal control subjects (Swift et al 1994, Mendelson et al 1979, and heavy drinkers (Davidson et al 1999) have shown the drug to produce substantial rates of both neuropsychiatric and gastrointestinal adverse effects. Overall, it seems that, irrespective of diagnosis, there are substantial numbers of individuals who experience dysphoria, nausea, and other poorly tolerated adverse effects of opioid blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research on individual responses to the effects of NTX may help to determine the relative importance of decreased craving for alcohol, decreased positive reinforcement induced by drinking, and aversive effects of the medication in reducing the risk of alcoholic relapse (Davidson et al 1999). Clinically, such information may also help in the development of methods to enhance patients' capacity to tolerate the medication.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of ATD on smoking behavior was measured via the following topography variables: time to first puff, number of puffs per cigarette, puff duration, interpuff interval, cigarette duration, and percentage of cigarette smoked. Acute changes in smoking topography and other drug consummatory behaviors have been found to reflect changes in drug motivation (Davidson et al, 1999;Renkin et al, 1979). Topography data were obtained by hand-timing the smoking behavior of participants who had been videotaped Effects of ATD on schizophrenic smokers B Hitsman et al while smoking.…”
Section: Modified Hamilton Depression Rating Scale (Mhamd)mentioning
confidence: 99%
“…NTX reduces alcohol consumption, craving, and relapse in subjects with a history of alcohol abuse (O'Brien et al, 1996;Anton et al, 1999;Davidson et al, 1999;Hernandez-Avila et al, 2006;see Heidbreder, 2005 for a recent review). Moreover, NTX significantly reduces ethanol consumption in rats (Stromberg et al, 1998) and monkeys (Boyle et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that NTX decreases the rewarding effect of alcohol intake (Swift et al, 1994;Volpicelli et al, 1995;Sinclair, 2001). Another possibility is that NTX reduces drinking by generating aversive side effects, such as nausea, when ethanol is consumed (Davidson et al, 1999;de Wit et al, 1999;McCaul et al, 2000;Mitchell et al, 2005a). However, there is also evidence that NTX significantly reduces alcohol craving in alcoholics during abstinence (Monti et al, 1999;Rohsenow et al, 2000;O'Malley et al, 2002), and improves resistance to thoughts, urges, and behaviors associated with drinking (Anton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%